Molecular characterization of a novel partitivirus isolated from Rhizoctonia solani - Chen, Xiangru; Yu, Zhaoyao; Sun, Yujia; Yang, Meipeng; Jiang, Ning (Frontiers in Microbiology, 2022)
Rhizoctonia solani is a widely distributed plant pathogen that can damage many crops. Here, we identified a novel mycovirus tentatively named Rhizoctonia solani partitivirus 433 (RsPV433) from an R. solani (AG3) strain which caused tobacco target spot disease on flue-cured tobacco. RsPV433 was consisted of two dsRNA segments with lengths of 2450 bp and 2273 bp, which encoded an RNA-dependent RNA polymerase and a coat protein, respectively. BLASTP results of RsPV433 showed that the closest relative of RsPV433 was Sarcosphaera coronaria partitivirus (QLC36830.1), with an identity of 60.85% on the RdRp amino sequence. Phylogenetic analysis indicated that RsPV433 belonged to the Betapartitivirus genus in the Partitiviridae family.